2020
DOI: 10.3390/atmos11050492
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost Air Quality Sensors: One-Year Field Comparative Measurement of Different Gas Sensors and Particle Counters with Reference Monitors at Tušimice Observatory

Abstract: With attention increasing regarding the level of air pollution in different metropolitan and industrial areas worldwide, interest in expanding the monitoring networks by low-cost air quality sensors is also increasing. Although the role of these small and affordable sensors is rather supplementary, determination of the measurement uncertainty is one of the main questions of their applicability because there is no certificate for quality assurance of these non-reference technologies. This paper presents the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 25 publications
3
31
1
1
Order By: Relevance
“…Comparison to the reference aerosol spectrometer (Grimm 1.108) showed that low-cost sensors, including PMS5003 used in this study, showed different performance than declared by the manufactures and provided a proper response in a limited range of bins [ 26 ]. On the other hand, the PMS series sensor showed a higher measurement quality than the Alphasense OPC-N2 (the previous model of the one used in our study) [ 27 ]. Contrary to this, Susan et al demonstrated that OPC-N2 sized particles identically and in good agreement with the reference, earlier mentioned, Grimm 1.108 aerosol monitor [ 28 ].…”
Section: Introductionmentioning
confidence: 79%
“…Comparison to the reference aerosol spectrometer (Grimm 1.108) showed that low-cost sensors, including PMS5003 used in this study, showed different performance than declared by the manufactures and provided a proper response in a limited range of bins [ 26 ]. On the other hand, the PMS series sensor showed a higher measurement quality than the Alphasense OPC-N2 (the previous model of the one used in our study) [ 27 ]. Contrary to this, Susan et al demonstrated that OPC-N2 sized particles identically and in good agreement with the reference, earlier mentioned, Grimm 1.108 aerosol monitor [ 28 ].…”
Section: Introductionmentioning
confidence: 79%
“…Custom PCBs can be rapidly designed to interface modules, sensor modules and other essential hardware together. All in all, this approach would enable rapid integration and real-world testing of the latest air pollution sensing modules as they hit the market [ 12 ]. The concept we just described goes beyond solving the burden of the lack of contextual data.…”
Section: Discussionmentioning
confidence: 99%
“…It was, therefore, selected and used extensively by the POLLUSCOPE project. Several Canarin II have also been deployed in the Johannine Library of Coimbra to monitor the impact of PM on its ecosystem, where the bat population has an essential role in the preservation of the library by eating the bookworms during the night [ 12 ]. These Canarin II are still acquiring data continuously to this date.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many PM sensors and detectors were developed during the last few decades to quantify the amount and size of PM that people are exposed to. These sensors range from very small and low cost [ 5 , 6 , 7 ] to large and bulky [ 8 ]. These sensors and detectors classify PM in sizes such as PM1, PM2.5, and PM10, where the number indicates the maximum size in micrometers.…”
Section: Introductionmentioning
confidence: 99%